Ultrasonography and Dandy-Walker malformation. - Farfán, José (2015)
A case of Dandy-Walker syndrome and then evaluated by postpartum prenatal sonographic control communicates. A cyst in the posterior fossa connected to the fourth ventricle and absence of cerebellar vermis was found at autopsy, in addition to moderate polyhydramnios and facial anomalies like micrognathia, rudiments of pinnae and held bilateral flexus adductus. Other related birth defects contribute to 90% of postnatal deaths. The Dandy-Walker syndrome can be diagnosed in utero by sonographic demonstration of characteristic morphological changes in the posterior fossa of the brain. The prenatal examination includes an assessment of supratentiorales defects and other extracranial defects. Coexist facial structural abnormalities and chromosomal abnormalities that often make a poor prognosis for survival.